Design and construction of a prototype vertical axis wind turbine (VAWT) for battery charging application - Thomas, Sunil; Riyan Khan, Mohammed Ashar; Chattopadhyay, Adhir Baran (International Journal of Engineering and Technology, 2018)
One of the major issues in this fast moving world is to meet the demand of energy in the most economical and environment friendly way. This research work on designing of a Vertical-axis wind turbines(VAWT) that gives a solution which is comparatively a cheap alternative of renewable energy. The Windmill rotates with sufficient wind, causing it to generate electricity owing to magnetic coupling between the rotating and stationary coil. The work demonstrates a vertical rotating prototype of windmill. The wind turbine can charge up to 12V battery. Advantage of this design is that it works without any consumption of fossil fuel and works efficiently in appropriate weather conditions without being closely monitored and the battery charges automatically without any harmful emissions or drawbacks. The work presented in this paper is an example of how natural resources like the wind energy can be used efficiently to produce electricity.